Metal concentrations in core HM17 at Holcroft Moss, Warrington, Cheshire, UK - Peter Ryan (22639724) (2025)
The data are metal concentrations from peat core HM17 from Holcroft Moss, Warrington, Cheshire, UK (British Grid Reference: SJ68462 93230). Contiguous 10mm thick slices of the peat core were freeze dried and then homogenised by grinding in an agate pestle and mortar. A subsample was taken and digested in 15.6 M HNO3 in closed vessels using a CEM Mars Xpress Microwave digester. Samples were ramped to 175C over 10 minutes, held for a further 15 minutes, and then allowed to cool, following the method outlined in US EPA 3051A. Determinations were measured by Inductively Coupled Plasma - Optical Emission Spectrometry (ICP-OES). There is no independent dating control on HM17, but a core at the same site, recorded a similar lead (Pb) profile, with a peak at 1920 +/- 20 AD. It is likely that the increase in the concentration of Pb and copper (Cu) from a depth of 220 mm reflects the atmospheric deposition of Pb and copper (Cu), from local metallurgical industries and increasingly from the combustion of fossil fuels (particularly coal) and from from the 17th century onwards.